Penggunaan Desmos dalam Memvisualisasikan Pembelajaran Matematika Bagi Guru MGMP Matematika Kabupaten Merauke - Abdul Rachman Taufik; Sadrack Luden Pagiling (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This training has the aim of introducing the Desmos page as a medium for learning mathematics and training teachers to use it in the learning process. Participants in this training were 15 teachers who were members of the Mathematics MGMP for SMP Kabupaten Merauke. The methods used are presentation, demonstration and practice. This training activity is divided into three stages: preparation stage, implementation stage and evaluation stage. The results obtained are that most of the training participants are proficient in operating the Desmos page and this training has provided new knowledge to visualize abstract Mathematical objects. With the completion of this training, it is hoped that all training participants can apply the Desmos page in the mathematics learning process.